Secular trends of the prevalence of emaciation, overweight, and obesity among school-aged children in Yunnan province, 1985–2019: A serial cross-sectional surveillance study in China - Yang, Yunjuan; Dai, Jing; Huang, Songquan; Li, Tunan; Song, Zhizhong; Zha, Shun; Ma, Chengpeng; Chang, Litao; Zhang, Song; Liu, Hong; Wei, Diexin; Yang, Fan; et al. (Frontiers in Nutrition, 2022)
Objective To understand the trends of nutrition in children and adolescents, which may further help to prevent and control chronic diseases in younger ages. Methods The Chinese National Surveys on Students' Constitution and Health (CNSSCH) in Yunnan is a survey of growth conditions, physical fitness, and health status of students in Yunnan and uses a series of complex multistage stratified sampling of seven prefectures consisting of 16 counties. Sampling schools were held constant over 35 years. The participants were randomly selected among 7–18 aged students. We used data from 1985, 1991, 2000, 2005, 2010, 2014, and 2019 CNSSCH of Yunnan. According to body mass index (BMI) criteria of National Working Group for Obesity in China (WGOC-BMI criteria), a participant's nutrition (emaciation, overweight or obesity) was defined. This study is based on survey data from 129,520 participants in 1985 (n = 14,683), 1991 (n = 4,894), 1995 (n = 6,673), 2000 (n = 9,751), 2005 (n = 23,461), 2010 (n = 22,889), 2014 (n = 23,003) and 2019 (24,166). Results Since 1985, the trends of emaciation over 35 years were decreasing. Regardless of gender, area, and age, the prevalence of obesity and overweight were increased. The average annual growth rate of overweight and obesity was quicker in rural areas and boys than in urban areas and girls. In Yunnan, emaciation, overweight, and obesity disparity in children were common phenomena, with differences in areas and gender. Conclusion Children in Yunnan faced the triple burden of malnutrition (emaciation, overweight, and obesity). We should take comprehensive policies and effective intervention measures to decrease the rate of nutrition deficiencies in school-aged children.